1985
DOI: 10.1136/pgmj.61.718.685
|View full text |Cite
|
Sign up to set email alerts
|

Normal thyrotrophin response to intravenous thyrotrophin releasing hormone administration: the best index of optimal L-thyroxine therapy in primary hypothyroidism

Abstract: Summary:Normalization of basal thyrotrophin (TSH) level is used as the endpoint in L-thyroxine (L-T4) therapy ofprimary hypothyroidism. However, several reports have questioned the reliability of this index because of seasonal variation of TSH. Therefore, we studied 85 consecutive patients with primary hypothyroidism over a period of 3.5 y. In these patients, TSH response (ATSH) to intravenous thyrotrophin releasing hormone (TRH) administration was examined when basal TSH was normalized with L-T4 therapy. Eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…Patients with the presence of any concomitant chronic disorder as well as those who were receiving chronic administration of other medications were excluded, since thyroid hormone metabolism is well documented to be disrupted resulting in altered circulatory thyroid hormone concentrations in presence of nonthyroidal illnesses (Chopra, Chopra, Smith, Reza and Solomon 1975;Chopra and Smith l975;Nomura, Pittman, Chambers, Buck and Shimizu 1975;Pittman, Suda, Chambers and Ray 1979;Fujii, Akai, Tanaka, Nakatani, Kinoshita, Seki and Wada 1981;Kabadi, Premachandra andMaayan 1982;Wartofsky and Burman 1982;Kabadi and Premachandra 1983;Kabadi and Premachandra 1984). All subjects were euthyroid as reflected by normal T4, T3 and basal TSH concentration as well as normal TSH response to IV TRH administration as described previously (Kabadi 1985;Kabadi and Rosman 1987). The healthy status of the subjects at the time of study was further confirmed by an absence of acute disorder, normal physical examination, normal blood chemistries and urinalyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with the presence of any concomitant chronic disorder as well as those who were receiving chronic administration of other medications were excluded, since thyroid hormone metabolism is well documented to be disrupted resulting in altered circulatory thyroid hormone concentrations in presence of nonthyroidal illnesses (Chopra, Chopra, Smith, Reza and Solomon 1975;Chopra and Smith l975;Nomura, Pittman, Chambers, Buck and Shimizu 1975;Pittman, Suda, Chambers and Ray 1979;Fujii, Akai, Tanaka, Nakatani, Kinoshita, Seki and Wada 1981;Kabadi, Premachandra andMaayan 1982;Wartofsky and Burman 1982;Kabadi and Premachandra 1983;Kabadi and Premachandra 1984). All subjects were euthyroid as reflected by normal T4, T3 and basal TSH concentration as well as normal TSH response to IV TRH administration as described previously (Kabadi 1985;Kabadi and Rosman 1987). The healthy status of the subjects at the time of study was further confirmed by an absence of acute disorder, normal physical examination, normal blood chemistries and urinalyses.…”
Section: Methodsmentioning
confidence: 99%
“…We previously suggested that hyperglucagonemia may be one of the factors responsible for low serum T3 and high serum rT3 concentrations observed in 'euthyroid sick' states (Kabadi, Premachandra andMaayan 1982;Kabadi This study was supported by research grants from Veterans Administration and Narveen Medical Research Foundation, St. Louis, Missouri.…”
Section: Introductionmentioning
confidence: 96%
“…There has been much debate regarding the significance of undetectable TSH concentrations in patients taking thyroxine replacement who are considered clinically to be euthyroid. Although few studies have demonstrated over-exposure of tissues other than the pituitary to thyroxine, several reports have advocated maintaining pituitary responsiveness toTRH (Evered et al, 1973;Squire & Gimlette 1982;Wehman et al, 1983;Davis et al, 1984;Kabadi, 1985). It is now possible to measure basal TSH levels by sensitive assays which can predict the response to TRH in most of these patients (Spencer et al, 1986;Wheatley et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Thyrotropin‐releasing hormone stimulation test was performed at this time in which serum TSH concentrations were determined before as well as 30 and 60 minutes after IV administration of TRH (500 μg). Thyroid‐stimulating hormone response (ΔTSH) was noted to be within normal range established in our laboratory (5 to 25 μ U/mL) 6 . The patient was readministered “disalcid” 3 g/day for six weeks and thyroid function tests as well as serum salicylate concentrations were evaluated by the same commercial laboratory as done initially.…”
Section: Case Reportmentioning
confidence: 81%